Peran Media Sosial dalam Revitalisasi Wayang Golek sebagai Media Pelestarian Budaya dan Dakwah Islam: Kajian Studi Literatur - Fairuz Sausan Kamil; Elvira Rismaya Putri; Fathiyah Azahra; Deni Ramdani; Fuad Shofwan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of digital technology and social media provides both opportunities and challenges for the preservation of traditional arts such as Wayang Golek from West Java, which is rich in cultural, moral, and Islamic preaching values. Wayang Golek has long served as a medium for da'wah, conveying religious teachings creatively through artistic performances. However, changes in the preferences of younger generations who favor instant digital content put this traditional art at risk of being forgotten. This study uses a qualitative method with a literature study approach to examine the role of social media in revitalizing Wayang Golek as a medium for cultural preservation and Islamic da'wah. The research results show that social media such as YouTube, Instagram, and TikTok play an important role in expanding access and public interest, especially among young people, through interactive and engaging educational content. However, limitations in technological proficiency and lack of support are major obstacles. Social media. It not only functions as a tool for communication and entertainment but also serves as a means of documentation and cultural education that can build virtual communities and a strong cultural identity. This study recommends strengthening digital training for artists, cross-sector collaboration, and creative content innovation to maintain the relevance and sustainability of Wayang Golek in the modern era. Adapting digital technology is an important strategy to align the preservation of traditional arts with the development of the times without losing the essence of cultural values and the messages contained within.